DEVELOPMENT OF PROJECT-BASED LEARNING (PJBL)-BASED STUDENT WORKSHEETS (LKPD) ON INSPIRATIONAL STORY TEXT MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Meylani, Aulia; Budiman, Budiman (Universitas Muhammadiyah Makassar, 2025)
Indonesian language instruction at the junior high school level often faces challenges in creating contextual and meaningful learning activities for students. One innovative solution that can be applied is the use of student worksheets (LKPD) based on project-based learning (PJBL) to enhance student engagement and learning outcomes. This study aims to develop PJBL-based LKPD for the Indonesian language subject in Grade IX at SMP Muhammadiyah 47 Sunggal that meets the criteria of validity, practicality, and effectiveness. This is a development research employing the ADDIE. The research subjects were Grade IX students and an Indonesian language teacher. Data collection techniques included expert validation (content, media, and language), practicality questionnaires for teachers and students, and a post-test to evaluate the effectiveness of the product. The data were analyzed using descriptive quantitative methods. The results show that the developed PJBL-based LKPD met the criteria of being highly valid in terms of content, design, and language; highly practical based on responses from teachers and students; and highly effective in improving student learning outcomes. These findings have important theoretical and practical implications. Theoretically, this study contributes to the literature on PJBL-based instructional material development. Practically, the developed LKPD can serve as an innovative and relevant learning resource to enhance the quality of Indonesian language instruction at the junior high school level